Ramelteon used to treat insomnia can reduce the occurrence of osteoporosis - Duygu Köse; Zekai Halıcı; Muhammed Yayla; Muhammed Ali Gürbüz; Adem Maman; Ahmet Köse (Acta Medica Alanya)
Aim: Melatonin promoted osteoblast differentiation and causes an increase in levels of markers of bone differentiation and proliferation. Ramelteon (RAMEL) activates melatonin receptors and binds to these receptors as non-selective. In this study, we investigated the preventive effects of the melatonin agonist RAMEL on osteoporosis by radiological, histological, and molecularly.Methods: Groups 1: Control, Group 2: Osteoporosis: Overectomized group (OP), Group 3: OP + ramelteon 2 mg/kg, Group 4: OP + ramelteon 4 mg/kg. 24 animals underwent bilateral ovariectomy. RAMEL was administered orally once a day in the prophylactic treatment mode for 8 weeks, 6 weeks after ovariectomy.Results: Fourteen weeks after ovariectomy, there was a significant reduction in femoral bone mineral density (BMD) (g/cm2) in the OP group compared to the control group. Compared to the OP group, RAMEL treatment significantly increased the BMD level (p<0.05). Bone matrix protein 2 (BMP2) and runt-related transcription factor 2 (RUNX2) mRNA levels were significantly lower in the OP group than in the control group (p<0.05). RUNX2 and BMP2 mRNA levels were significantly higher in the RAMEL treatment groups than in the OP group (p<0.05).Conclusion: To take advantage of the peripheral effects of melatonin, RAMEL, a peripheral melatonin agonist, can be used to prevent osteoporosis.